The Effect of Location and Price on Customer Satisfaction of Sharia Cafe - Sutrisno Sutrisno; Maulana D.Tanjung (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2021)
This research aims to determine the effect of location and price on customer satisfaction partial and simultaneous at sharia café. This research uses a quantitative approach with primary data. The population in this research were customers of Sharia Café in Dapoer Fezdaf Café Syariah Belitung. This research used the purposive sampling method with 80 respondents. The analytical method used is multiple linear regression to test the hypothesis with the SPSS version 22 programs. The results showed that (1) location has a significant positive effect on customer satisfaction (2) price has a significant positive effect on customer satisfaction (3) The location and price simultaneously have a significant positive effect on customer satisfaction. Café Syariah is proven to satisfy its customers by using two approaches of choosing a location according to the customer's choice and determining the price according to the customer's wishes